CONCEPTUAL METAPHORS IN MYLO XYLOTO ALBUM BY COLDPLAY - Kamaliah, Selvia Neilil (2013)
This study entitled 'Conceptual Metaphors in Mylo Xyloto Album by Coldplay' investigates Conceptual Metaphor (CM) and the types of CM that are used in Mylo Xyloto song lyrics as well as the possible reasons that can be generated from the uses of the metaphors. The study uses the song lyrics of Coldplay's album entitled Mylo Xyloto as data. In analyzing the data, the qualitative method especially a case study is used. Furthermore, the data are analyzed using the framework of the Conceptual Metaphor Theory (CMT) (Lakoff and Johnson, 1980a, 1980b, 1980c; Kovesces, 2002, 2010). The study found that the dominant conceptual metaphors used are about life, love, and changes, namely LIFE IS JOURNEY, CHANGES ARE MOVEMENT, LIGHT IS A FLUID, PURPOSES ARE DESTINATION, LOVE IS A UNITY, LOVE IS WAR, LOVE IS STRUGGLE, VISUAL FIELDS ARE CONTAINERS, ACTIVITIES ARE SUBSTANCES, STATES ARE LOCATIONS, LESS IS DOWN, and BAD IS DOWN. The conceptual metaphors are categorized as structural (68.9%), ontological (17.8%) and orientational (13.3%) metaphors. This occurrences lead to the conclusion of four possible reasons. The song writer uses the metaphors to support the issue of freedom and struggle and to persuade to do something, to share his values, to show that what we experience in daily life can be seen as a container and substance, and to evaluate events as something good or bad. Keywords: Conceptual Metaphors Theory (CMT), song lyrics, Coldplay.